Textbook of Hyperbaric Medicine - Jain, Kewal K. (Springer International Publishing : Imprint: Springer, 2017)
This comprehensive volume captures the latest scientific evidence, technological advances, treatments and impact of biotechnology in hyperbaric oxygen therapy. Divided into three distinct sections, the book begins with basic aspects that include history, equipment, safety and diagnostic approaches; this is followed by clinical applications for hyperbaric oxygen therapy in various modalities; the last section provides an overview of hyperbaric medicine as a specialty with best practices from around the world. Integration of multidisciplinary approaches to complex disorders are also covered. Updated and significantly expanded from previous editions, Textbook of Hyperbaric Medicine, 6th Edition will continue to be the definitive guide to this burgeoning field for students, trainees, physicians and specialists. .
Keywords: Medicine.; Internal medicine.; Medical biochemistry.; Rehabilitation.; elektronické knihy; electronic books